Public Opinion About Adverse Childhood Experiences: Social Stigma, Attribution of Blame, and Government Intervention. (August 2022) - Purtle, Jonathan; Nelson, Katherine L.; Gollust, Sarah E.
Adverse childhood experiences (ACEs) are receiving increasing attention in academic, policy, and media discourses. However, no public opinion research has focused on ACEs. We conducted a nationally representative survey of U.S. adults to address this knowledge gap. A web-based survey was conducted using the Ipsos KnowledgePanel ( N = 503, completion rate = 60.5%) in fall 2019. We found that inter-personal stigma and parental blame related to ACEs were prevalent, with 25.0% of respondents unwilling to have a person with "a lot of ACEs" as a close co-worker and 65.2% believing that parents were very much to blame for the consequences of ACEs. Fifty percent of respondents believed that government intervention to prevent ACEs was very important. After adjustment for demographic characteristics, inter-personal stigma toward people with ACEs and conservative ideology were significantly associated with lower perceived importance of government intervention to prevent ACEs. Black race, Hispanic ethnicity, and female gender were significantly associated with higher perceived importance of government intervention. These findings provide an empirical foundation to inform strategies to communicate ACE science to public and policymaker audiences.